Infantile wheeze: rethinking dogma. Issue 4 (4th October 2016) - de Benedictis, Fernando Maria; Bush, Andrew
Abstract : Wheeze is a common symptom in young children and is usually associated with viral illnesses. It is a major source of morbidity and is responsible for a high consumption of healthcare and economic resources worldwide. A few children have a condition resembling classical asthma. Rarer specific conditions may have a wheezy component and should be considered in the differential diagnosis. Over the last half century, there have been many circular discussions about the best way of managing preschool wheeze. In general, intermittent wheezing should be treated with intermittent bronchodilator therapy, and a controller therapy should be prescribed for a young child with recurrent wheezing only if positively indicated, and only then if carefully monitored for efficacy. Good multidisciplinary support, attention to environmental exposition and education are essential in managing this common condition. This article analyses the pathophysiological basis of wheezing in infancy and critically discusses the evolution of the scientific progress over time in this unique field of respiratory medicine.